Structure, conduct and performance of the Malaysian meat and meat preparation industry - Mohamed, Zainal Abidin; Kasron, Norzalila; Abd Latif, Ismail; Sharifuddin, Juwaidah; Rezai, Golnaz; Terano, Rika (Universiti Putra Malaysia Press, 2015)
Higher concentration tends to be inefficient in the allocation of resources especially in price setting and probable collusion among larger firms. One of the most influential approaches among various theories of industrial organisation is the Structure-Conduct-Performance (S-C-P) model, which highlights the competitive conditions of an industry by examining the structure of the industry in relation to behaviour (conduct) and performance of companies. Thus, the objective of the study is to investigate the level of concentration and industry performance of selected meat and meat preparation manufacturing sub-sectors in Malaysia and to examine the relationship between market structure, conduct and performance of the industry. Secondary data were collected from selected meat manufacturing firms registered under the CCM. Results indicate that the meat processing industry tended to have a moderate concentration with monopolistic market structure prevailing throughout the study period, where more than 60% of the industry market share is being controlled by four firms. Results from the TSLS regression technique indicate that market structure provides a weak effect on advertising. This indicates that the lower the concentration ratio of the industry, the higher the expenditure spent on advertising in order to attract customers to buy products. Consequently, increases in advertising expenses have a positive effect on a firm's profit. Thus, there is a direct relationship between market structure, conduct and performance with positive and significant feedback effect among the variables; however, the magnitude of the feedback varies.